Dolomite rejection from crushed pebble phosphate by attrition scrubbing. (November 2019) - Puvvada, S.; Thompson, P.; Miller, J.D.
Highlights: Dolomite rejection by size separation at 53 µm after attrition scrubbing. Characterization of samples using ICP and XCT analysis. The effect of time, temperature, pH, and rpm on dolomite rejection. Chemical analysis reported for the 53 × 20, 20 × 7 and minus 7 µm size classes. Evaluation of the XCT grain size distribution with respect to liberation. Abstract: The degradation of resource quality, coupled with an increase in resource consumption, impose significant challenges on the capability of phosphate mineral processing operations to supply acceptable products at a rapid rate to fertilizer plants. A serious ongoing concern for phosphate mining operations is to produce a product containing sufficiently low dolomite content (<1% MgO) for the efficient and economic production of fertilizers. This has motivated the detailed characterization and inspection of phosphate resources to identify the textural/morphological features that may limit recovery in mineral processing operations. For example, high speed X-ray computed tomography (HSXCT), and high resolution X-ray computed tomography (HRXCT) have been used for 3D analysis of pebble phosphate. We now apply these results to evaluate attrition scrubbing, a promising method for dolomite rejection from central Florida pebble phosphate, the major source of phosphate in the US. Attrition scrubbing of pebble phosphate samples (top size of 1 mm and 2.97% MgO grade) has been performed under different conditions of scrubbing time, pH, temperature and rpm. The samples subjected to scrubbing were wet screened at 53 µm and the chemical analyses (ICP analyses) of the coarse and fine products indicate that scrubbing can help in the rejection of fines, which contain a significant amount of MgO. The best scrubbing results were obtained for a scrubbing time of 20 min, and an MgO content in the coarse product (concentrate) of approximately 1.72%, with a phosphate P2 O5 recovery of 63.47%. It is evident from these results that the phosphate concentrate (+53 µm) from scrubbing does not meet the required MgO level as desired for further processing by acidulation. Further, for a particular scrubbing test, the minus 53 µm was subjected to further size separation at 20 µm and 7 μm. Particle size and chemical analyses are reported for the scrubbed fractions, including 53 × 20 µm, 20 × 7 µm, and −7 µm size classes. Results suggest that considerable liberation of dolomite from the pebble phosphate may be expected at a particle size of 20 µm.